Effect of Yeast Cell Wall on Gut Health, Immunity and Milk Production of Dairy Cattle in Normal and Heat Stress Conditions. Review - Mahasneh , Ola K.; Abdelqader, Anas; Al-Fataftah , Abdur-Rahman A. (Jordan Journal of Agricultural Sciences, 2023)
This review focuses on the most recent literature to bring to light the major beneficial effects of the yeast cell wall (YCW) and its products on dairy cattle. These products include viable yeast, yeast culture, nutritional yeast, and fractionated yeast products. The yeast cell wall is one of these products and belongs to the fractionated yeast products used to promote production performance and health in dairy cows. The yeast and YCW were proven to have positive impacts on dairy cattle performance in terms of milk yield, milk components, and overall quality. As well, these products showed beneficial effects under heat stress conditions. The YCW is a natural fermentation derivative of yeast cells such as Saccharomyces cerevisiae species consists mainly of β-glucan (29% to 64%), mannan (31%), and some other compounds like protein (13%), lipids (9%), chitin (1–2%) with β-glucan and mannan being the main bioactive molecules. The mode of action through which YCW elicit their beneficial functions in dairy cow explain their effect on cows’ metabolism and digestion, immunity, rumen and intestine health, and subsequent performance and well-being. These modes of action include improving gastrointestinal (GI) tract health, stimulating immune system components as it is considered an immunomodulator additive, mycotoxin binding ability, and improving antioxidant capacity. Therefore, yeast and YCW products are one of the promising areas of ruminant nutrition in dairy cows, not only because of their nutritional and health benefits to dairy cows but also due to their negligible residual effects on dairy cows’ bodies and products.